Overexpression of mGluR7 in the Prefrontal Cortex Attenuates Autistic Behaviors in Mice - Wang, Xiaona; Gao, Chao; Zhang, Yaodong; Hu, Shunan; Qiao, Yidan; Zhao, Zhengqin; Gou, Lingshan; Song, Jijun; Wang, Qi (Frontiers in Cellular Neuroscience, 2021)
Autism spectrum disorder (ASD) is associated with a range of abnormalities pertaining to socialization, communication, repetitive behaviors, and restricted interests. Owing to its complexity, the etiology of ASD remains incompletely understood. The presynaptic G protein-coupled glutamate receptor metabotropic glutamate receptor 7 (mGluR7) is known to be essential for synaptic transmission, and is also tightly linked with ASD incidence. Herein, we report that prefrontal cortex mGluR7 protein levels were decreased in C57BL/6J mice exposed to valproic acid and BTBR T+Itpr3tf/J mice. The overexpression of mGluR7 in the prefrontal cortex of these mice using a lentiviral vector was sufficient to reduce the severity of ASD-like behavioral patterns such that animals exhibited decreases in abnormal social interactions and communication, anxiety-like and stereotyped/repetitive behaviors. Intriguingly, patch‐clamp recordings revealed that the overexpression of mGluR7 suppressed neuronal excitability by inhibiting action potential discharge frequencies, together with enhanced action potential threshold and increased rheobase. These data offer a scientific basis for the additional study of mGluR7 as a promising therapeutic target in ASD and related neurodevelopmental disorders.